Efektivitas Terapi Pernapasan Pursed Lips Dan Posisi Semi Fowler Pada Penderita Tuberkulosis - Beleneti, Sri; Syamsuddin, Fadli (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: : Pulmonary tuberculosis patients will experience shortness of breath. Breathing muscles in patients who experience shortness of breath can work when there is an abnormality in respiration. Interventions that can be done to reduce shortness of breath in patients with pulmonary tuberculosis are pursed lips breathing and semi-fowler position. Methods: The research design used in this study was pre-experimental with a one-group pre-post test design approach, the sample used was 14 tuberculosis patients. Results: The results of the study obtained a sig value or p-value in the group given pursed lips breathing obtained 0.008 <0.05 which indicates that pursed lips breathing therapy is effective in reducing the shortness of breath of tuberculosis patients, the sig value or p-value in the group given the semi fowler position obtained 0.014 <0.05 which indicates that the semi fowler position is effective in reducing the shortness of breath of tuberculosis patients. Conclusion: : Of this study is that the administration of pursed lips breathing and semi-fowler position is equally effective in reducing the shortness of breath experienced by tuberculosis patients.